ANALISIS KESIAPAN GURU DALAM PELAKSANAAN KURIKULUM MERDEKA DI TK PERTIWI 1 KOTA JAMBI - Alfina Damayanti; Pratika Rindriani; Fadila Aulia; Tasya Girsang; Sri Indriani Harianja; Winda Sherly Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to see the readiness of Pertiwi 1 Kindergarten teachers, Jambi City, Danau Sipin District, Jambi City Regency in implementing the independent curriculum. Teacher readiness is the attitude and willingness to be involved in the tasks of educating, teaching, guiding, directing, training, assessing and evaluating students. The method in this research uses qualitative methods by collecting data through interviews, observation and document analysis. The results of this research show that the majority of teachers at Pertiwi 1 Kindergarten, Jambi City show readiness in implementing the Independent Curriculum. They understand the planning or preparation process carried out by teachers before teaching, such as making lesson plans and preparing teaching materials, learning resources and learning media.